The Role of Stakeholders and Mechanism of Forest Area Gazettement of Gunung Birah Protected Area - Ady Prasetya Nugraha; Syarifuddin Kadir; Eko Rini Indrayatie (TROPICAL WETLAND JOURNAL, 2018)
The gazettement of forest area is one of the significant aspects in forest designation that should be carried out to determine the legal framework regarding with the administrative and the physical status as well as forest boundaries. It is expected that the legal framework and precise forest area will support the powerful and purposeful forest management. The study aimed to find out the roles and the standpoints of stakeholders, to explore the mechanism, to identify and analyze the obstacles in the process, to formulate alternative effort in the process of forest area gazettement of Gunung Birah Protected Forest. It is expected that this study will enrich the concern on forestry policy especially regarding with the gazettement of the forest area, as well as provide the input to the ministry of forestry and local government in formulating strategies and policies in the implementation of forest area gazettement. The result indicated the stakeholders involved in the gazettement of Gunung Birah protected forest in KPHP Model Tanah Laut as well as their roles are the functionaries of KPHP Model Tanah Laut, local community adjacent to the forest area, regional office of forestry Planning (Balai Pemantapan Kawasan Hutan/BPKH), Local Government (The administration committee of forest boundary), and Central Government(the ministry of Environment and forestry). Constraints in the affirmation process of Gunung Birah protected forest areas in KPHP Tanah Laut can be divided into internal and external factors. Internal constraints include human errors in the compilation of Minute of Forest Boundary, incomplete implementation document thus the gazettement could not be processed, and the lack of socialization dealing with forest boundary to the local community adjacent to forest area. Meanwhile, the external constraints were the determination of forest boundaries stretch frequently intersects with settlement or other rights, the overlapping use of an area, the lack of public recognition on forest area boundary, the issuance of private land rights certificate in forest areas, and diverse interpretations on the status of forest area.